Cutis marmorata telangiectasia congenita-a needle in the neonatal dermatology haystack? - Hassan Shakeel; Ather Ahmed (Global Journal of Rare Diseases - Peertechz Publications, 2020)
Cutis Marmorata Telangiectasia Congenita (CMTC, also known as van Lohuizen syndrome) is a rare disorder characterised by dilatation of the cutaneous vasculature. This results in a blue-purple 'marbled' appearance of the skin due to telangiectasia, phlebectasia and persistent cutis marmorata. It is often mistaken for benign cutis marmorata and is therefore likely underdiagnosed. CMTC can occur in connection with other dysmorphic findings in several syndromes (e.g. Adams-Olivers) or in isolation. We review the evidence surrounding the epidemiology, pathophysiology and management of isolated CMTC, and contextualize it with a case.